Penetapan Kadar Alkaloid Total Pada Batang Brotowali (Tinospora Crispa L.) Secara Spektrofometri UV-Vis - Puspa Indah; Ali Rakhman Hakim; Tuti Alawiyah; Kunti Nastiti (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2026)
Brotowali stem (Tinospora crispa L.) is a plant that grows abundantly in Central Kalimantan and has been empirically used for generations as an antidiabetic remedy by the Dayak Ngaju community. Brotowali stem contains secondary metabolite compounds, including alkaloids, which possess various pharmacological activities, one of which is antidiabetic activity. This study aimed to determine the alkaloid content of Tinospora crispa stem extract in aquadest, ethyl acetate, and n-hexane fractions. The research employed an observational descriptive method by analyzing qualitative data through color reaction tests and quantitative data using UV-Vis spectrophotometry to determine alkaloid levels. The qualitative analysis results showed positive color reactions indicating the presence of alkaloid compounds. Quantitative analysis using UV-Vis spectrophotometry revealed that the total alkaloid content in the aquadest fraction was 20.19 mg or 20.19%, in the n-hexane fraction was 20.54 mg or 20.54%, and in the ethyl acetate fraction was 31.07 mg or 31.07%. The highest total alkaloid content was found in the ethyl acetate fraction. In conclusion, the extract of Tinospora crispa stem positively contains alkaloids, with the highest alkaloid content obtained in the ethyl acetate fraction at 31.07%.